2015
DOI: 10.1111/clr.12621
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soft tissue healing at implants and teeth: a study in a dog model

Abstract: The healing process around teeth and implants follows a similar sequence of events. Nevertheless, the complete process of healing and maturation of the peri-implant tissues takes longer than around teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(71 reference statements)
0
8
0
2
Order By: Relevance
“…This outcome revealed that the peri‐implant biologic width followed the shape of the abutment design, but with similar dimensions. Other studies demonstrated that irrespective of the implant design (Abrahamsson, Berglundh, Wensström, & Lindhe, ) or after type of resective surgery (Sukekava et al, ), the epithelial and connective tissue components will arrange with similar dimensions. In contrast, other studies reported that the vertical position of the implant shoulder according to the bone crest (Farronato et al, ) and the implant macrodesign (Becker et al, ) could influence the length of the epithelium attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This outcome revealed that the peri‐implant biologic width followed the shape of the abutment design, but with similar dimensions. Other studies demonstrated that irrespective of the implant design (Abrahamsson, Berglundh, Wensström, & Lindhe, ) or after type of resective surgery (Sukekava et al, ), the epithelial and connective tissue components will arrange with similar dimensions. In contrast, other studies reported that the vertical position of the implant shoulder according to the bone crest (Farronato et al, ) and the implant macrodesign (Becker et al, ) could influence the length of the epithelium attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of peri‐implant epithelial and connective tissue dimensions are a representative evaluation of the peri‐implant biologic width (Cochran et al, ; Sukekava, Pannuti, Lima, Tormena, & Araujo, ). Previous studies demonstrated that the establishment of peri‐implant biologic width on a dental implant with a horizontal offset configuration led to different outcomes at the implant shoulder/abutment interface (Canullo et al, ; Canullo et al, ; Canullo et al, , Rocha et al, , Strietzel, Neumann, & Hertel, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A tight biological sealing may not only improve soft tissue integration but also prevent bacterial invasion. 27 To achieve this goal, the PDA coatings had been successfully deposited on the preactivated Ti surface by self-polymerization. After preactivation, the Ti with micro-and nano-structure and high hydrophilic should be more suitable for PDA deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Ο ηονζυηενμξ πανάβμκηαξ πμο επζδνά ζηδκ πενζειθοηεοιαηζηή αοπεκζηή μζηζηή απμννυθδζδ ιεηά ηδκ ζφκδεζδ ημο δζααθεκκμβυκζμο ημθμαχιαημξ είκαζ δ ιζηνμαζαηή ιζηνμδζείζδοζδ ζημ ιζηνμηεκυ, δ ελάθεζρδ ημο μπμίμο ιε ημπζηά ακηζιζηνμαζαηά ιέζα ακαιέκεηαζ κα δχζεζ πμθθά οπμζπυιεκα απμηεθέζιαηα. Ακ ηαζ δεκ έπεζ ηαηακμδεεί πθήνςξ μ ιδπακζζιυξ ηδξ ημπζηήξ ακηζιζηνμαζαηήξ δνάζδξ ημο ανβφνμο, είκαζ βκςζηυ υηζ μ άνβονμξ δζαεέηεζ ακηζιζηνμαζαηή ηαζ ααηηδνζμηηυκμ δνάζδ έκακηζ αενυαζςκ, ακαενυαζςκ, Gram-εεηζηχκ ηαζ Gram-ανκδηζηχκ ααηηδνίςκ, ιοηήηςκ, ζχκ, ζοιπενζθαιαακμιέκςκ ηαζ πμθοακεεηηζηχκ ζηεθεπχκ υπςξ μ ακεεηηζηυξ ζηδκ ιεεοηζθθίκδ S. aureus (Sukekava et al, 2015). Σα απμηεθέζιαηα ηδξ ιεθέηδξ ζε πνυκμ επμφθςζδξ 12 εαδμιάδςκ έδεζλακ 2.8 mm ιέζμ ιήημξ πενζειθοηεοιαηζημφ αθεκκμβυκμο, 1.7 mm ιέζμ ιήημξ πνμζπεθοηυημξ επζεδθίμο ηαζ 1.5 mm ιέζμ φρμξ ζοκδεηζημφ ζζημφ, ηζιέξ ιζηνυηενεξ απυ αοηέξ ηδξ πανμφζαξ ένεοκαξ.…”
unclassified